Effect of lactose Intolerance on Oral Health by Estimating Some Biochemical Parameters - Ahmed, Shaimaa Essa (American Journal of Bioscience and Clinical Integrity, 2026)
There are several signs and symptoms of lactose intolerance. Alactasia can be acquired over time, but it can also be congenital. This illness affects around 65% of people worldwide from birth. Upon additional examination, it is discovered that almost 70% of adult East Asians are lactose intolerant. The study examines lactose intolerance globally, with a focus on the data that is currently accessible for Europe. According to the European Dairy Association, lactase insufficiency was more common than 40% in Hungary, Estonia, Greece, and Italy. Studies on the issue in Bulgaria are insufficient. We provide the first findings from a questionnaire study carried out in Bulgaria. It was determined whether the individuals' ethnicity and potential lactose intolerance were related. Information on how eliminating lactose-containing foods (milk and dairy products) might improve dental health is provided and explored. Here is a list of foods that people who are lactose intolerant can utilize to safeguard their dental health. Aim of the study to assess the potential effects of lactose intolerance on oral health. We take 25 patient of lactose intolerance (10 males and 15 females) and also take 20 normal persons (10 males and 10 females). The ages of study groups ranging from 15 – 35 year. Our study was done in Tikrit Teaching Hospital in Tikrit city from 1st of November 2024 to the end of February 2025. All subjects (patients and controls) were examined for dental problems. There was no significant difference of age between patient and control groups (P value 0.5) because we take almost similar ages between these two groups. There was a highly significant decrease (P value 0.001) of vitamin D3 and calcium in patients as compared with control 20 groups, and this may be related to the restriction of dairy materials in foods of lactose intolerant patients. It's unclear how lactose intolerance and dental health are related. It seems that the connection between lactose intolerance and dental health has not been thoroughly studied up to this point. To further investigate and validate the impact of lactose intolerance on dental health, further high-level evidence studies are needed.